Pengembangan Vidio Pembelajaran Berbasis Aplikasi CapCut Pada Materi Sistem Pernapasan Manusia - Fanny, Vio; Harahap, Risma Delima; Hasibuan, Rosmidah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop a learning video based on the CapCut application which contains material explaining the respiratory system in humans equipped with sound and images. This research is the development of the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation). The ADDIE model includes five stages, however, in this research only three stages were applied, namely analysis, design and development. This research was carried out at SMP Negeri 1 Pangkatan. The subjects of this research were media experts, material experts in the field of biology, and students in class VII5 of SMP Negri 1 Pangkatan. This type of research data is qualitative data and quantitative data. Validation was carried out by media experts and material experts in the field of biology. The validation results show that the learning video is classified as